2001
DOI: 10.1053/euhj.1999.2581
|View full text |Cite
|
Sign up to set email alerts
|

A clinical appraisal of left atrial function

Abstract: The left atrium modulates left ventricular filling through three components: a phase of reservoir or expansion during systole, a conduit phase during diastole, and an active contractile component (when sinus rhythm is present) during late diastole. This active contractile component of the left atrium has an important role in patients with ventricular dysfunction as a 'booster pump' to augment ventricular volume. Augmented left atrial booster function is one of the mechanisms compensating for decreased early fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
250
1
16

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(269 citation statements)
references
References 99 publications
2
250
1
16
Order By: Relevance
“…21) The LA modulates LV diastolic filling and increases cardiac performance. 22) During exercise, the LA reservoir and active pumping function are augmented, nevertheless, its conduit facilities remain unchanged. 9) To maintain LV filling at an optimum level during hemodynamic changes, the LA reservoir, conduit, and pumping function should work in harmony.…”
Section: Discussionmentioning
confidence: 99%
“…21) The LA modulates LV diastolic filling and increases cardiac performance. 22) During exercise, the LA reservoir and active pumping function are augmented, nevertheless, its conduit facilities remain unchanged. 9) To maintain LV filling at an optimum level during hemodynamic changes, the LA reservoir, conduit, and pumping function should work in harmony.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in anesthetized dogs (15) and pigs (4) atrial compliance was found to decrease during the transition from sinus rhythm (SR) to AF. Because during AF fibrillatory contractions continuously spread over the atrial myocardium, the compliance of the fibrillating atrium is generally lower than the diastolic atrial compliance during SR (11). However, the long-term effect of a loss of atrial contractility due to AF on compliance and size of fibrillating atria has not been studied yet.…”
mentioning
confidence: 99%
“…We showed that both levosimendan and dobutamine increased AEF, which expresses LA systolic function and is analogous to LV ejection fraction (25,26). However, levosimendan, but not dobutamine, improves PEF, which reflects the passive emptying of the LA into the LV during early diastole.…”
Section: Discussionmentioning
confidence: 97%